NIKAH ONLINE: KAJIAN KOMPARATIF FIQH KLASIK DAN FATWA MADZHAB DALAM HUKUM ISLAM - Ulhiyah Ulhiyah (SAMAWA, 2024)
The phenomenon of online marriage has become an important discussion within the realm of Islamic law, raising questions about the consistency of religious values with technological advancements. In this context, this paper aims to analyze the perspectives of classical fiqh and fatwas within the framework of Islamic law related to online marriage. Using a comparative analysis approach, the author considers views from various fiqh schools and fatwas to explore the consistency of Islamic law with modern technological developments.